Locus of Control and Job Satisfaction with Work Life Balance as Mediation - Doni Oktavian; Fatkhurahman; Bambang Supeno (Yayasan Education Al Aqsho Modern, 2023)
This study aims to determine the effect of locus of control on job satisfaction mediated by work-life balance. This research is explanatory research that uses quantitative techniques to test hypotheses empirically. The population in this study were all Civil Servants (PNS) who were staff at the Riau DPRD Secretariat, totaling 188 employees. The number of samples in this study was taken using purposive sampling. So that the number of samples in this study was 188 employees. Data collection techniques using a questionnaire. The hypothesis in this study was tested using SEM-PLS analysis through the SmartPLS version 3.0 software. The results of the study show that the External Locus of Control has a positive effect on job satisfaction. Internal Locus of Control has a positive effect on job satisfaction. External Locus of Control has a positive effect on Work-Life Balance. Internal Locus of Control has a positive effect on Work-Life Balance. Work-Life Balance has a positive effect on job satisfaction. External Locus of Control has a positive effect on job satisfaction mediated by Work-Life Balance. External Locus of Control has a positive effect on job satisfaction mediated by Work-Life Balance.